Postcoital finesse. - Clyne, J; Miesenböck, G (2009)
Mating changes female reproductive behavior in profound ways. In Drosophila, the trigger for this behavioral switch is a small peptide called sex peptide (SP), which is transferred with the male seminal fluid during insemination. Two papers in this issue of Neuron (Häsemayer et al. and Yang et al.) show that SP inhibits a small set of internal sensory neurons in the female genital tract. These neurons project to the CNS to control the female's reproductive behavior.